Estetika Timur Dalam Teater Tradisional Kemidi Rudat Lombok (Jurnal Sitakara, 2023)
This study aims to determine eastern aesthetics in the traditional theater of Kemidi Rudat Lombok. The problem is focused on eastern aesthetic values ​​in Kemidi Rudat traditional theatrical performances as one of the arts that expresses aesthetic values ​​originating from cultural nobility. In order to address this problem, references to Soetarno's theory are used in a book on thoughts on eastern aesthetics which are more oriented to spirituality/spirits and moods. The data were collected through observation, interviews and documentation. This study uses a qualitative-descriptive approach using the semiotic analysis method of Tedeusz Kowzan theater. In summary and clearly this study shows that the eastern aesthetic values ​​of the Komidi Rudat theater include: 1) stoicism which is a reflection of the nature of human character which has the principle of maturity in thinking and acting, 2) adigang-adigung which is the antithesis of haughty nature and arrogance that should not be carried in humans. 3) item-putek which is the nature of human optimism in defending the truth and goodness (pute/white) and against bad and evil (item/black). 4) jiwe seli which is the nature of human concern in doing everything, that every work and problem can be solved together/cooperation. 5) sect which is human nature that has knowledge and a clear mind, and 6) manut which is human nature that obeys orders and rules.Keywords: Eastern Aesthetics, Traditional Theatre, Kimidi Rudat.